Research in orthopedics and traumatology at the present stage - Korolkov, Oleksandr; Golubeva, Inna; Bengus, Lyudmila; Maltseva, Valentyna; Pogorelaya, Anna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is devoted held in Kharkiv, Ukrainian scientific-practical conference "Modern research in orthopedics and traumatology" which took place in Kharkiv on October 30-31, 2014.